Towards care-centred societies - Spangenberg, Joachim H.; Lorek, Sylvia (Frontiers in Sustainability, 2024)
Care work, often considered as economically non-productive, is undervalued and professionally underpaid. This short perspective paper develops a holistic understanding of care, including paid and unpaid care work. It contributes to identifying pathways towards socially an environmentally sustainable, low consumption societies. Based on archetypical definitions from feminist literature and gender studies, political science, sociology, psychology, ecological economics and our own work in consumption analysis we define care work as comprising activities and practices in relation to someone or something (e.g. the environment) which are nurturing and cultivating land, plants, animals, humans, and social groups to support wellbeing and quality of life. They do so by providing many of the "services" that enable people to participate in society, and sustain objects of ethical, emotional, and relational value. The definition covers a broad spectrum of care work, including both professional paid care and unpaid, more or less voluntarily provided care (social norms constitute the "less voluntary" case). We differentiate among different types of care work and use this more fine grain approach to have a closer look at the relation of paid and unpaid care and the relation of care to sustainable development.